OVERVIEW OF THE CONDITION OF SANITATION FACILITIES WHERE FOOD MANAGEMENT AT SULTAN HASANUDDIN INTERNATIONAL AIRPORT MAKASSAR - Dwi Ayu Angriany Muchtar (Sean Institute, 2020)
Food management places in Sultan Hasanuddin International Airport Makassar include restaurants and restaurants, canteens, cafes, shops and so on. One of the health requirements of food management that is important and affects the quality of sanitary hygiene is sanitation facilities. While the producers pay more attention to how to produce and serve good food and do not pay too much attention to the problem of sanitation facilities. This is behind to examine the problem of sanitation facilities because sanitation facilities that do not meet health requirements will facilitate the occurrence of food contamination by microorganisms such as bacteria, fungi, viruses and parasites and chemicals that can pose a risk to health. This research aims to find out the condition of sanitation facilities where food management is located at Sultan Hasanuddin International Airport Makassar in 2012. This type of research is observational with descriptive approach methods. Population and sample of 29 food management places. Observation sheet questionnaires used to collect data. The data is processed using the spss 16.0 program and presented in the form of tables and narratives. Results from the study showed that the provision of clean water in all water conditions used 29 (100%) qualified. Sewage sewers are 20 (69%) eligible and 9 (31%) ineligible. 16 (55.2%) were eligible and 13 (44.8%) were ineligible. 7 (24.1%) qualified and 22 (75.9%) ineligible. There were 28 (96.6%) eligible and 1 (3.4%) ineligible. From the results of the study it can be concluded that the water used has been qualified, sewerage, trash cans and equipment washes have mostly qualified while handwashing places are mostly not qualified. It is recommended to the government to make sanitary hygiene regulations where special food management of the airport and it is expected to the angkasa pura to make improvements and provide proper sanitation facilities.